TALE Transcription Factors in Sweet Orange (Citrus sinensis): Genome-Wide Identification, Characterization, and Expression in Response to Biotic and Abiotic Stresses - Peng, Weiye; Yang, Yang; Xu, Jing; Peng, Erping; Dai, Suming; Dai, Liangying; Wang, Yunsheng; Yi, Tuyong; Wang, Bing; Li, Dazhi; Song, Na (Frontiers in Plant Science, 2022)
Three-amino-acid-loop-extension (TALE) transcription factors comprise one of the largest gene families in plants, in which they contribute to regulation of a wide variety of biological processes, including plant growth and development, as well as governing stress responses. Although sweet orange (Citrus sinensis) is among the most commercially important fruit crops cultivated worldwide, there have been relatively few functional studies on TALE genes in this species. In this study, we investigated 18 CsTALE gene family members with respect to their phylogeny, physicochemical properties, conserved motif/domain sequences, gene structures, chromosomal location, cis-acting regulatory elements, and protein–protein interactions. These CsTALE genes were classified into two subfamilies based on sequence homology and phylogenetic analyses, and the classification was equally strongly supported by the highly conserved gene structures and motif/domain compositions. CsTALEs were found to be unevenly distributed on the chromosomes, and duplication analysis revealed that segmental duplication and purifying selection have been major driving force in the evolution of these genes. Expression profile analysis indicated that CsTALE genes exhibit a discernible spatial expression pattern in different tissues and differing expression patterns in response to different biotic/abiotic stresses. Of the 18 CsTALE genes examined, 10 were found to be responsive to high temperature, four to low temperature, eight to salt, and four to wounding. Moreover, the expression of CsTALE3/8/12/16 was induced in response to infection with the fungal pathogen Diaporthe citri and bacterial pathogen Candidatus Liberibacter asiaticus, whereas the expression of CsTALE15/17 was strongly suppressed. The transcriptional activity of CsTALE proteins was also verified in yeast, with yeast two-hybrid assays indicating that CsTALE3/CsTALE8, CsTALE3/CsTALE11, CsTALE10/CsTALE12, CsTALE14/CsTALE8, CsTALE14/CsTALE11 can form respective heterodimers. The findings of this study could lay the foundations for elucidating the biological functions of the TALE family genes in sweet orange and contribute to the breeding of stress-tolerant plants.